2017
DOI: 10.5194/hess-21-3199-2017
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring soil moisture from middle to high elevation in Switzerland: set-up and first results from the SOMOMOUNT network

Abstract: Abstract. Besides its important role in the energy and water balance at the soil–atmosphere interface, soil moisture can be a particular important factor in mountain environments since it influences the amount of freezing and thawing in the subsurface and can affect the stability of slopes. In spite of its importance, the technical challenges and its strong spatial variability usually prevents soil moisture from being measured operationally at high and/or middle altitudes. This study describes the new Swiss s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 64 publications
(109 reference statements)
1
28
0
Order By: Relevance
“…Finally, spatial soil moisture variability is reported for soils of different texture, structure, porosity, and macroporosity. A higher sand content was previously reported to increase drainage and decrease storage capacity at the satellite footprint scale (Panciera 2009). In this study, significant increase of the forecast goodness could be identified for the high and the low sand content groups which demonstrates the importance of accounting for local to regional variations in the soil properties.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, spatial soil moisture variability is reported for soils of different texture, structure, porosity, and macroporosity. A higher sand content was previously reported to increase drainage and decrease storage capacity at the satellite footprint scale (Panciera 2009). In this study, significant increase of the forecast goodness could be identified for the high and the low sand content groups which demonstrates the importance of accounting for local to regional variations in the soil properties.…”
Section: Discussionmentioning
confidence: 74%
“…The site comprises a full meteorological station, continuous soil moisture measurements and a permanent ERTM profile (Hilbich et al, 2008a;Pellet and Hauck, 2017;PERMOS, 2016b;Rosset et al, 2013 spatial variability of permafrost temperatures and active layer depth (cf. Fig.…”
Section: Stockhorn (Sto)mentioning
confidence: 99%
“…Since then the borehole only exhibits seasonal freezing. Due to its spatially heterogeneous internal air circulation and the feedback with vegetation and moisture, DRE is however considered an important location at the permafrost limit (Morard et al, 2008(Morard et al, , 2010Pellet and Hauck, 2017), and used in this investigation for comparison with ERTM data from the other network sites.…”
Section: Dreveneuse (Dre)mentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 6), for example, support the results of a soil moisture analysis in Switzerland suggesting that around 2000 m a.s.l., the regime 410 controls change from precipitation/evaporation to more frost-affected (Pellet and Hauck, 2017). In this respect, another potential future application of DFI may be the separation of snowmelt and glaciermelt contributions to streamflow with an additional breakpoint.…”
Section: Technical Aspects Of Delayed Flow Separationmentioning
confidence: 99%